The vegetal germplasm base bank Tibaitata Research Center - Cerón L. , Maria del Socorro; Valbuena B., Raúl Iván; Moreno M., José Dilmer (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2018)
The Group of Genetic Resources and Crop lmprovement (GRGMV in spanish) of Corpoica, is a strategic Group of research and support far the agricultura! development of the country, based on the appraisal, conservation and sustainable use ofthe agro biodiversity.